Review of the oriental Issid genus Tetricodes Fennah (Hemiptera: Fulgoroidea: Issidae) with the description of one new species - Zhang, Zhengguang; Chen, Xiangsheng (Zootaxa, 2009)
Species in the genus Tetricodes Fennah, 1956 (Hemiptera: Fulgoroidea: Issidae: Parahiraciini) are reviewed. The genus consists of two species: T. polyphemus Fennah, 1956 and T. songae Zhang & Chen, sp. nov.. The male of T. polyphemus Fennah, collected from Leigongshan National Natural Reserve, Leishan, Guizhou Province, and Pianma, Lushui, Yunnan Province, is reported and described for the first time. The generic characteristics are redefined. The main morphological characters and male genitalia of the two species are described, or redescribed, and illustrated. A key to species in the genus is provided.